Emergent Attentional Bias Toward Visual Word Forms in the Environment: Evidence From Eye Movements - Zhao, Jing; Yang, Hang; Weng, Xuchu; Wang, Zhiguo (Frontiers in Psychology, 2018)
Young children are frequently exposed to environmental prints (e.g., billboards and product labels) that contain visual word forms on a daily basis. As the visual word forms in environmental prints are frequently used to convey information critical to an individual’s survival and wellbeing (e.g., “STOP” in the stop sign), it is conceivable that an attentional bias towards words in the environment may emerge as the reading ability of young children develops. Empirical findings relevant to this issue, however, are inconclusive so far. The present study examines this issue in children in the early stages of formal reading training (grades 1, 3, and 5) with the eye-tracking technique. Children viewed images with word and non-word visual information (environmental prints) and images with the same words in standard typeface on a plain background (standard prints). For children in grade 1, the latency of their first fixations on words in environmental prints were longer than those in standard prints. This latency cost, however, was markedly reduced in grades 3 and 5, suggesting that in older children an attentional bias towards words has emerged to help filter out the non-word visual information in environmental prints. Importantly, this attentional bias was found to correlate moderately with word reading ability. These findings show that an attentional bias towards visual word forms emerges shortly after the start of formal schooling and it is closely linked to the development of reading skills.